Study of Water Quality of Kedung Jumbleng River As A Liquid Waste Disposal of Tofu Industry and Community Behavior of The People in Krajan, Mojosongo, Surakarta - Primadi Gayuh Laksono Putro; H. Hadiyanto (Diponegoro University, 2022)
This study examines the water quality of the Kedung Jumbleng River which is used as a tofu liquid waste disposal site and the behavior of the surrounding community which aims to find out how the water quality of the Kedung Jumbleng River is, community behavior, and steps to control pollution. The study was identified through literature searches or field observations formulated in research questions: (1) How is the water quality of the KedungJumbleng river? ; (2) How is the behavior of the people in Krajan Mojosongo, Surakarta and (3) What are the steps to control pollution. This study is a descriptive mix method with a sequential explanatory design approach, and uses research data collection methods with field surveys and mapping and laboratory tests with parameters such as temperature, pH, BOD, COD, DO, TSS, and NH3. The sampling technique used was purposive sampling. The analysis used to determine water quality is the Pollution Index method. Descriptive analysis method is used to determine people's behavior in terms of knowledge, attitudes and actions. The results showed that the water quality of the Kedung Jumbleng river exceeded the quality standard in several water quality parameters. Pollution Index value for all classes of moderately polluted water. The results of the analysis of community behavior showed that the behavior of the people around the Kedung Jumbleng river had knowledge aspects of 55.1% High, 42.9% Enough, and only 2% had low knowledge. Attitude aspects 26.6% Good, 69.4% Fairly Good, and 4% Bad. Aspects of action 53% Good and 47% Poor. Based on the interpretation of the research results, it can be concluded that: (1) The water quality of the Kedung Jumbleng river is currently moderately polluted; (2) The behavior of the community in Krajan Mojosongo Surakarta is quite good in terms of the value of the aspects of knowledge, attitudes and actions.